2021
DOI: 10.1186/s12884-021-03701-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in the free maternal healthcare era in sub-Saharan Africa: a scoping review of providers’ and managers’ perceptions

Abstract: Background Free maternal healthcare financing schemes play an essential role in the quality of services rendered to clients during antenatal care in sub-Saharan Africa (SSA). However, healthcare managers’ and providers’ perceptions of the healthcare financing scheme may influence the quality of care. This scoping review mapped evidence on managers’ and providers’ perspectives of free maternal healthcare and the quality of care in SSA. Methods We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [ 73 ]. This is in line with a review study on maternal health that noted that poor reimbursement from the government contributed to charges in health facilities and poor quality maternal health care in the sub-Saharan African region [ 74 ]. It is, therefore, very important that health system gaps are addressed, in order to motivate women to access health care.…”
Section: Discussionsupporting
confidence: 88%
“…Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [ 73 ]. This is in line with a review study on maternal health that noted that poor reimbursement from the government contributed to charges in health facilities and poor quality maternal health care in the sub-Saharan African region [ 74 ]. It is, therefore, very important that health system gaps are addressed, in order to motivate women to access health care.…”
Section: Discussionsupporting
confidence: 88%
“…Another study has shown that women who worried about the lack of health care providers at health facilities were not likely to complete optimal doses of SP [72]. This is in line with a review study on maternal health that noted that poor reimbursement from the government contributed to charges in health facilities and poor quality maternal health care in the sub-Saharan African region [73]. It is therefore very important that health system gaps are addressed, in order to motivate women to access health care.…”
Section: Discussionsupporting
confidence: 59%
“…However, this has been shown in some other SSA countries. This mismatch could partly be attributed to delayed seeking of healthcare services for childbirth care and inadequate quality of care received [32][33][34]. Factors such as demotivated health workers due to poor remuneration, increased workload on health workers, limited availability of essential medical supplies and low quality pre-service and refresher training may partly explain the inadequate quality of care [29,32,33].…”
Section: Discussionmentioning
confidence: 99%